A State-Level Examination of the Association Between Home and Community-Based Services and Rates of Nursing Home Residency With Special Attention to Nutrition Programs - Buys, David R. (J Nutr Gerontol Geriatr, 2012)
Federal food and nutrition programs implemented by the Administration on Aging and funded by the Older Americans Act (OAA) seek to enable older adults to remain in their homes and communities through a comprehensive, coordinated, and cost-effective array of services. We hypothesized that expenditures devoted to nutrition programs for home and community-based nutrition services were inversely related to changes in state-level rates of institutionalization for older adults from one year to the next, such that states that spend more money per capita on community-based nutrition programs would have smaller increases or greater decreases in rates of institutionalization, controlling f1or expenditures on other home and community based services (HCBS). We found, however, that there was not an effect of OAA Nutrition Services on the change in rates of nursing home residency. We noted, though, that states which direct a greater proportion of their long-term care expenditures to home and community based services appear to have more reduction in their rates of nursing home residency. Further longitudinal work at the state and individual levels is warranted.